Antígeno (Australiano) asociado a la hepatitis en el Perú - Garrido Pinson, Gerardo (1973)
630 subjects, divided in four groups, were investigated for the presence of hepatitis-associated (Australia) antigen using the technique of Counterimmunoelectrophoresis. Group l, made-up by 500 normal subjetcs, 300 of them living at Lima, at sea Level, and 100 in Cerro de Pasco, at 4,200 meters above sea level, no positivy was found in those subjects; in the 100 that lived at Iquitos, in the Amazoniam Jungle, a 3% of positivy was found. Group ll, formed by 100 patients with clinical and biochemical diagnosis of acute hepatitis was sub-divided in three groups: in the first one were 40 patients under twenty years old, only one of them was positive; in the second ther were 55 patients over twenty years old, with 30 positives (54.5%) and the third there were five cases of epidemic hepatitis all negatives. Group lll included 9 patients with histological diagnosis of chronic aggresive hepatitis and 6 of chronic persistent hepatitis, all negatives. Group IV conformed by 15 patients with histological diagnosis of primary liver carcinoma, two were positives (13.33%).